PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK PADA MATERI BANGUN DATAR DI SDN 143 PALEMBANG - Sugianti, Novita; Darwin Effendi; Hj. Noviati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Developing water-related materials is a step to improve the learning process for students. This research aims to develop and produce teaching material products in the form of flipbook-based emodules for grade 3 students at SD Negeri 143 Palembang which educators can use in the learning process. This research was carried out at SD Negeri 143 Palembang in Class 3C. The development model used in this research is the ADDIE model. Data collection techniques in this research include interviews, tests, questionnaires, and documentation. The validity results consisted of material experts, media experts and language experts who obtained 90% results in the very valid category. The feasibility results from educators obtained a 96% rating in the very feasible category. The difference between the learning outcomes of students who had not used the module (with an average score of 3.29) and those who used it (with an average score of 97.67) was significan. The effectiveness results obtained from the pretest and posttest showed an N-Gain of 0.96 in the very effective category.